CURAHAN WAKTU KERJA PADA USAHA TERNAK KAMBING - Handayani, Sayekti (FAPETKAN UNTAD, 2014)
The objective of this study was to determine the amount of family working time of goat farming as well as the influencing factors. It was conducted in the District of East Palu. Sampling locations and respondents were determined by purposive sampling based on the highest number of goat. A total of 40 respondents were selected from two villages. The collected data were analyzed using Ordinary Least Square (OLS). The results showed that the amount of working time on goat farming were 193.39; 102.32; 58.93 of working days equivalent to man per year for husband, wife, and child respectively could be substituted each other. The goat farming became the main occupation from farmers working time point of view compared to other work that as a source of family income. Factors that have affected the husband working time were working time and income outside of goat farming as well as children working time and the number of goats. Meanwhile, the influencing factors of wife working time were age and working time outside the goat farming.Keywords : Family working time, goat farming, ols.